(3GdLhQ GdaQjO aj QSe GdbQBf GdeLjOs - (3SjO HQcGJ Hf jhSa oZQjTI GdghQjfjs; (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s
(3ChdgG (B:s
(3GeG HYO adeG cGf Yde GdQSe ef Cge GdegeGJ hGdJaMU ajg ef GdhGLHGJ ef SjeG QSe GdbQBf GdhGQO Yf GdEeGe SjOfG YKeGf Hf YaGf haj gPG GdYde s
(3BNQgG (B:s
(3HHQcI gPg GdCSeGA hGdCMQa hGddg SHMGfg hJYGdi CYde hgPG BNQ eG jSQg Gddg JYGdi Hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B29 - (3U(B86s
(3GdfSNI HgG MhGTs
(3LejdI CQHGH GdebGUO GdeSeGI H` (B"(3JZQjO GdLejdI defGOeI GdYbjdI hgj TQM d`(B"(3YbjdI CJQGH GdbUGFO aj CSfi GdebGUO(B" (3ddTGWHj GfXQ cTa GdXfhf L(B2 (3U`(B1159s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdbQGAGJ hGdJLhjOs